Estrogen Receptors and Estrogen-Induced Uterine Vasodilation in Pregnancy: A Review - Jin Bai; Yan Li; Ronald R. Magness; Dong-bao Chen (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Normal pregnancy is associated with dramatic increases in uterine blood flow to facilitate the bidirectional maternal–fetal exchanges of respiratory gases and to provide sole nutrient support for fetal growth and survival. The mechanism(s) underlying pregnancy-associated uterine vasodilation remain incompletely understood, but this is associated with elevated estrogens, which stimulate specific estrogen receptor (ER)-dependent vasodilator production in the uterine artery (UA). The classical ERs (ER\(α\) and ER\(β\)) and the plasma membrane-bound G protein-coupled ER (GPR30/GPER) are expressed in UA endothelial cells and smooth muscle cells, mediating the vasodilatory effects of estrogens through genomic and/or nongenomic pathways that are likely epigenetically modified. This chapter aims to summarize the literature on UA ERs with a focus on their roles in mediating the local UA production of vasodilators by estrogens and pregnancy and to deliberate on the potential clinic implications of dysregulated ER-mediated estrogen signaling in hypertensive pregnancy complications. The activation of these three ERs by estrogens enhances the endothelial production of nitric oxide (NO), which has been shown to play a key role in uterine vasodilation during pregnancy. However, the local blockade of NO biosynthesis only partially attenuates estrogen-induced and pregnancy-associated uterine vasodilation, suggesting that mechanisms other than NO exist to mediate uterine vasodilation. We summarize here the literature on the role of NO in ER-mediated mechanisms controlling estrogen-induced and pregnancy-associated uterine vasodilation and our recent work on a “new” UA vasodilator hydrogen sulfide (H2S) that has dramatically changed our view of how estrogens regulate uterine vasodilation in pregnancy.